Analisis Profil Literasi Matematis Siswa SMA Pada Materi Barisan Dan Deret Berbasis Level PISA - Zahratul Amri; Al Jupri (Jambura Journal of Mathematics Education, 2026)
Mathematical literacy is an essential competence that students must acquire to solve problems situated in real-life contexts. However, numerous studies indicate that students’ mathematical literacy levels remain relatively low. This study aims to describe senior high school students’ mathematical literacy abilities in the topic of sequences and series and to identify their difficulties based on the distribution of test scores and the mathematical literacy processes involved. This research employed a descriptive design. The participants were tenth-grade senior high school students selected through purposive sampling. Data were collected using a mathematical literacy test developed based on the PISA framework and were analysed through item score distribution analysis and qualitative analysis of students’ responses. The results indicate that the majority of students are at low to moderate levels of mathematical literacy. The analysis of score distribution per item reveals that students’ difficulties increase along with the complexity of the required mathematical literacy processes. The most prominent difficulty was found in the formulating process, which subsequently affected students’ performance in the employing and interpreting processes. In addition, limited prior mathematical knowledge also hindered students’ performance in the employing process. These findings provide a clear profile of students’ mathematical literacy and their difficulties, and may serve as a basis for teachers in designing instructional strategies that better support the development of mathematical literacy skills.